Non-tariff barriers in Malaysia's agricultural sector / Azlina Hanif, Rokiah Alavi - Hanif, Azlina; Alavi, Rokiah (2011)
The present paper describes the incidence of non-tariff measures in the country's agricultural sector from 1978 to 2007. The level of NTB protection is then measured using the frequency method. The measurements reveal that the level of protection has generally increased over the years. Significant increases in the protection level are observed in 1987 and 2004. Despite being a developing country, the trend of agricultural NTB protection appears to be similar to the trend of protection in developed market economies that provide significant protection to their agricultural sectors.